Standard Audit File for Tax (SAF-T) in the Digital Age: Accountants’ Perspectives on Tax Compliance, Audit Efficiency and Financial Reporting Transparency - Cruz, J.; Lopes, A.I.; Narciso, A. (XX Congresso Interacional de Contabilidade e Auditoria, 2025)
Originally proposed by the OECD, the Standard Audit File for Tax (SAF-T), emerged as a standardized digital reporting format aimed at facilitating structured data exchange between businesses and tax authorities. SAF-T stands out as an important component of fiscal modernization in Portugal, particularly through its two modules: SAF-T for Invoicing, which is mandatory and integrated with platforms such as e-Fatura, and SAF-T for Accounting, which, although legally defined, has seen its enforcement postponed due to implementation challenges. Despite its potential to simplify compliance and enhance financial oversight, the dual application of SAF-T has created new organizational, operational, and technical constraints, especially for small and medium enterprises. Its wider implementation is still challenged by problems like taxonomy mapping, data consistency, and software compatibility. This dissertation investigates how Portuguese accounting professionals perceive the effectiveness and limitations of both SAF-T formats. The findings reveal differentiated experiences and readiness levels, highlighting the need for greater training, simplified reporting tools, and supportive regulatory guidance to ensure successful integrations of SAF-T into everyday accounting practice.